Unbundling, regulation and pricing: Evidence from electricity distribution - Sven Heim; Bastian Krieger; Mario Liebensteiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Unbundling of vertically integrated utilities has become an integral element in the regulation of network industries and has been implemented in many jurisdictions. The idea of separating the network, as the natural monopoly, from downstream retailing, which may be exposed to competition, is still subject to contentious debate. This is because there is much empirical evidence that unbundling eliminates economies of vertical integration while empirical evidence on price reducing effects is still lacking. In this paper we study the effect of legal unbundling on grid charges in the German electricity distribution industry. Using panel data on German distribution system operators (DSOs) we exploit the variation in the timing of the implementation of legal unbundling and the fact that not all DSOs had to implement unbundling measures. We are also able to identify heterogeneous effects of legal unbundling for different types of price regulation, because we observe a switch in the price regulation regime from rate-of-return regulation to incentive regulation during our observation period. Our findings suggest that legal unbundling of the network stage significantly decreases grid charges in the range of 5% to 9%, depending on the type of price regulation in place.
Keywords: D22; L11; L22; L51; L94; Q48; 330; Vertical Integration; Electricity Distribution; Unbundling; Regulation